RANCANG BANGUN WEBSITE JURUSAN ILMU PEMERINTAHAN FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS PALANGKA RAYA - Jadiaman Parhusip; Deddy Ronaldo; Hanna Darmawan (JURNAL TEKNOLOGI INFORMASI, 2019)
The Government Science Department is under the auspices of the University of Palangka Raya Faculty of Social and Political Sciences (FISIP), requiring facilities / media to manage academic data and information in the form of websites.The methods used in making the website are: data collection, consultation and design design methods using UML-Based Web Engineering (UWE). The website was developed using PHP, Xampp, Adobe Dreamweaver CS3, Notepad ++, Adobe Photoshop, and MYSQL.Website testing uses blackbox testing to test system functionality and browser testing for testing web pages using internet explorer, mozilla firefox and google chrome. The more appropriate display result is to use Google Chrome. Users of this website are admin, course coordinator lecturers, editorial team of journals, students and visitors